Spring-mass behavior during exhaustive run at constant velocity in elite triathletes - Rabita, G.; Slawinski, J.; Girard, O.; Bignet, F.; Hausswirth, C. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The aims of this study were i) to evaluate changes in leg-spring behavior during an exhaustive run in elite triathletes and ii) to determine whether these modifications were related to an increase in the energy cost of running (Cr).